ONTOGENETIC AGE AND INOCULATION METHODS FOR THE IN VITRO ESTABLISHMENT OF Eucalyptus pilularis Smith (Nativa, 2023)
We aimed to evaluate the in vitro establishment of nodal segments of Eucalyptus pilularis Smith considering two origins of tissues (Or1 - epicormic shoots collected from pruned branches of selected adult trees; Or2 - shoots collected from seminal mini-stumps) and four inoculation methods (Me1 - culture medium supplemented with 0.5 g L-1 activated charcoal; Me2 - culture medium supplemented with 800 mg L-1 PVP30; Me3 - exposure to light for 30 days; Me4 - exposure to dark for 7 days). At 30 days after the in vitro inoculation of tissues, there was no establishment of tissues from epicormic shoots (Or1). Or2 resulted in lower percentages of tissue oxidation and contamination by microorganisms, in addition to having presented establishment and formation of shoots. Me1 resulted in a lower mean tissue oxidation, although it differed statistically only from Me4. An origin of the tissues of ontogenetic age was a determining factor for the successful in vitro establishment of E. pilularis. The use of the Or2 origin and the Me1, Me2, and Me3 methods are recommended to reduce phenolic oxidation of tissues in the in vitro establishment.Keywords: antioxidant agents; exposure to light; epicormic shoots; tissue oxidation. Idade ontogenética e métodos de inoculação para o estabelecimento in vitro de Eucalyptus pilularis Smith RESUMO: Objetivou-se avaliar o estabelecimento in vitro de segmentos nodais de Eucalyptus pilularis considerando duas origens de tecidos (Or1 - brotos epicórmicos coletados em galhos podados de matrizes adultas e Or2 - brotos coletados de minicepas seminais) e quatro métodos de inoculação (Me1 - meio de cultura suplementado com 0,5 g L-1 de carvão ativado, Me2 - meio de cultura suplementado com 800 mg L-1 de PVP30, Me3 - exposição à luminosidade por trinta dias e Me4 - exposição em ambiente com ausência de luminosidade por sete dias). Aos 30 dias após a inoculação in vitro dos tecidos, constatou-se que não houve estabelecimento de tecidos oriundos da Or1. A utilização de segmentos nodais provenientes da Or2 resultou em menores percentuais de oxidação e de contaminação por microrganismos, além de ter apresentado estabelecimento e emissão de brotos. O uso do Me1 resultou em menor média de oxidação, embora tenha diferido estatisticamente somente do Me4. A origem dos tecidos associada à idade ontogenética foi um fator determinante para o sucesso do estabelecimento in vitro de E. pilularis. Recomenda-se a utilização da Or2 e dos métodos Me1, Me2 e Me3 a fim de reduzir a oxidação fenólica dos tecidos durante o estabelecimento in vitro.Palavras-chave: agentes antioxidantes; exposição à luminosidade; brotos epicórmicos; oxidação de tecidos.